ANALISIS PERBANDINGAN KEPUASAN KONSUMEN ATAS PELAYANAN MINIMARKET INDOMARET DAN ALFAMART DI WILAYAH DUKUHWALUH (A VOMPARATIVE ANALYSIS OF COSTUMER STATIFACTION ON THE SERVICE OF INDOMARET AND ALFAMART MINIMARKET IN DUKUHWALUH) - Umiyati Umiyati; Suyoto Suyoto (Media Ekonomi, 2014)
The aimost this research were: 1) to find out whether there was any difference on consumers stratification of indomaret and alfamart m,inimarket in Dukuhwaluh area. 2) to find out the differing factor on consumers stratification of indomaret and alfamart minimarket in Dukuhwalu area. This research used primary data gained from questionnaire. The data was analyzed by compare means independent t test, descriptive analysis with SPSS program. The result of the research showed that the service quality of indomaret and alfamart minimarket was supposed to be good by most of their consumers. There was a significant difference in the comparison between indomaret and alfamart minimarket based on dimension of reliability, responsiveness, assurance, emphaty and tangible as well as the overall quality. Based on the t test result of indomaret and alfamart, responsiveness dimension was regarded as the responsiveness dimension was not suitable as expected eiyher by the consumers of alfamart or the consumers indomaret. It indicated that it needs the betterment of service quality, specially in responsiveness dimension. Keyword :consumers stratification, reliability, responsiveness, assurance, emphaty and tangible.